Analysis of autonomous vehicle storage and retrieval system by open queueing network - Heragu, S.S.; Xiao Cai; Krishnamurthy, A.; Malmborg, C.J. (2009 IEEE International Conference on Automation Science and Engineering, 2009)
Automated vehicle storage/retrieval system (AVS/RS) technology is a relatively new material handling technology. It is a flexible system that is a viable alternative to automated storage/retrieval systems (AS/RS). The manufacturing system performance analyzer (MPA) is an open queuing network (OQN) analyzer based on the parametric decomposition method. This paper models the AVS/RS and uses MPA to analyze the performance of an AVS/RS configuration. Experimental results are provided to show that the OQN methodology can be applied effectively to analyze an AVS/RS when vehicle utilization is between 60% and 85%. MPA is a better choice than simulation to quickly evaluate alternate configurations of the AVS/RS.